Andragoški zavod Maribor – Ljudska univerza 100 let (University of Maribor Press, 2022)
Maribor Adult Education Centre - People’s University 100 years. Andragoški zavod Maribor - People’s University is one of the oldest institutions for adult education in Slovenia. In 100 years, we have operated under various names and different social systems, but always for the needs of people in the local and wider community. At least in the last two decades, we have contributed a lot to the deepening of partnership cooperation and the integration of various institutions in the local and regional environment.